The effect of greenwashing awareness on consumer behaviour towards organically-labelled foods among generation Z Filipinos - Samaniego, Claire Anne D. (College of Home Economics, University of the Philippines Diliman, 2023)
The growing concerns of consumers on the environment, food safety, animal welfare, and human health have resulted in the increase in the interest and demand for organically-produced foods. However, with the rise of the green market, some companies capitalize on this opportunity for their personal interests, thus leading to greenwashing. The prevalence of greenwashing and with “organic” being ambiguous make consumers susceptible to being greenwashing victims. With the lack of existing local studies, the present study therefore aims to investigate the effect of greenwashing awareness as an intervention method on consumer behavior (i.e., organic label trust, perceived environmental impact, perceived impact on human health, willingness-to-purchase) towards organically-labeled foods among Generation Z consumers through an online pre- and posttest survey (n=193). The main reasons for consumption of organic food include healthy contents, freshness, environmental friendliness, and freedom from pesticides. Moreover, respondents rely on visual cues (i.e., labelling, logo) to determine organic food. In line with this, they prefer certified organic logos or seals over generic ones. Most respondents are unaware of the greenwashing practice, suggesting that they are at risk to become victims of greenwashing. Finally, for the effect of the intervention method, greenwashing awareness had a significant negative effect (p<0.0001) on the examined constructs of consumer behavior. Among the constructs, greenwashing exhibited the largest impact on trust, suggesting that it negatively impacts the relationship between consumers and sellers. It is recommended that government agencies strongly enforce organic labeling regulations and that companies avoid practicing greenwashing.